Disavowal and foundational fantasies: A psychosocial exploration of the class, race and the social construction of the sexual child in the Anglophone West. (September 2013) - Egan, R Danielle; Hawkes, Gail
Archival data offers rich source material for examining the complicated, and often paradoxical, deployment of the sexual child within protection literature crafted in the Anglophone West during the early 19th century. Drawing on a psychosocial framework, I analyze the affective and ideological subtext of social purity narratives in order to understand how and why it came to feel so natural for reformers and their primary audience – middle-class parents. I argue that the social construction of the sexual child within this discourse rests upon longstanding ideological preoccupations and middle class anxieties regarding class and race distinction. Attempts to secure the myth of middle-class purity through the disavowal of the middle-class child's autoeroticism functioned as a foundational fantasy in calls for protection. In the end, the construction of the sexual child within this protection movement was largely a figment of middle-class anxiety and defense, but one which nevertheless had and continues to have powerful cultural resonance.